Peran Metadata dalam Pengelolaan E-commerce - Eko Prasetyo; Muhammad Irwan Padli Nasution (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Metadata as structured data that has the function of defining, describing, organizing information with the aim of facilitating data management(Pratidina & Nasution, 2024). It is pretty much also referred to as one data against another data, one information against another information, playing a crucial role in various sectors, such as education, libraries, and also included in e-commerce management. This research article aims to explain the role and concept of metadata and its types that can be used in e-commerce systems. The writing of this research uses the literature review method. This method was chosen to explore existing knowledge to collect previous research results that are relevant to the topic discussed. The findings of this research found that metadata has an important role and its types can be used and developed further in e-commerce. The implication is that this research strengthens academic understanding that metadata is not only about data management but also supports the efficiency of information systems including in e-commerce.